Cognitive, Behavioral, and Emotional Disorders in Populations Affected by the COVID-19 Outbreak - Pera, Aurel (Frontiers in Psychology, 2020)
This review enhances the existing literature on the emotional and mental health of COVID-19 patients and affected persons who have spent prolonged time intervals in self-isolation or quarantine. My article cumulates previous research findings on adverse physical and psychological consequences developed from the COVID-19 pandemic. Throughout May 2020, I conducted a quantitative literature review of the Web of Science database, with search terms including “psychological anxiety,” “emotional distress,” “social isolation stress,” and “mental health disorders.” As I focused on research published exclusively this year, only 104 various types of articles met the eligibility criteria. By removing those whose results were inconclusive, unconfirmed by replication, or too general, and because of space constraints, I selected 49, mainly empirical, sources. The inspected collected findings prove that the COVID-19 pandemic has resulted in greater degrees of psychological distress in the affected populations. The COVID-19 outbreak may generate emotional distress and anxiety, aggravating preexisting mental health disorders and shaping stress-related disturbances for affected people. Individuals having severe mental illness tend to be hurt emotionally by social problems heightening their vulnerability. Both COVID-19 infected patients and the general affected population may develop severe depressive symptoms. Significant degrees of fear may heighten the damage generated by such a highly infectious disease. The volume of recovered patients may diminish COVID-19-related apprehension and panic. Future research should investigate whether COVID-19-related reduced care provision and prolonged self-isolation and quarantine will have long-term impact on mental and psychological health.